Patterns and correlates of preserved humoral immunity to vaccines in children following allogeneic hematopoietic stem cell transplantation. (16th December 2020) - Al‐Antary, Eman; Henry, Meret; Spruit, Jessica; Yankelevich, Maxim; Chu, Roland; Ravindranath, Yaddanapudi; Savaşan, Süreyya
Abstract: Data on preservation of vaccine immunity following allogeneic HSCT in children is limited. We investigated vaccine titers and sought correlations with patient characteristics in this study. Twenty‐eight cases were retrospectively analyzed. Antibody concentrations against hepatitis A, hepatitis B, 3 poliovirus serotypes, tetanus, diphtheria, measles, mumps, rubella, varicella, and 13 pneumococcus serotypes were measured as part of planned monitoring following HSCT. Protective antibody levels were found for hepatitis A in 79% of the recipients, measles in 54%, all poliovirus serotypes in 50%, tetanus in 50%, rubella in 50%, varicella in 46%, hepatitis B in 46%, mumps in 43%, diphtheria in 29%, and ≥7/13 pneumococcus serotypes in 46%; lowest level observed for diphtheria and highest for hepatitis A prior to starting post‐HSCT immunizations. In univariate analysis, patients with non‐malignant diseases ( P = .03) and without GvHD ( P = .04) had more protective titers. A significant positive association was found among vaccine titers against the microorganisms or the serotypes of the same microorganism, which were administered together in the same product, including polio serotypes, diphtheria and tetanus, mumps, measles, and rubella. Higher degrees of sero‐positivity are likely to be due to lack of prior chemotherapy in non‐malignant disease cases and lesser immunosuppression in patients without GvHD. Monitoring long‐term vaccine titers and administering vaccines accordingly could be evaluated for post‐HSCT re‐immunization practice.